2018
DOI: 10.1371/journal.pone.0190024
|View full text |Cite|
|
Sign up to set email alerts
|

Women’s reproductive health knowledge, attitudes and practices in relation to the Zika virus outbreak in northeast Brazil

Abstract: ObjectivesTo assess knowledge, pregnancy attitudes and contraceptive practices in relation to the Zika virus outbreak in Brazil. MethodsWe interviewed 526 women 18 to 49 years old in primary health services in a Northeastern capital of Brazil, in 2016. They provided information about their knowledge of Zika transmission and health consequences, their receipt of counseling related to sexual and perinatal transmission of Zika, their pregnancy intentions and reassessment of contraceptive options in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 15 publications
6
52
1
5
Order By: Relevance
“…Our findings are aligned with those described by Vilela Borges et al., who evaluated knowledge and attitudes about pregnancy and contraception in the context of Zika virus in Brazil. In that study, health officials informed the public about Zika virus transmission and its health consequences, and providers knew about the congenital syndrome, but knowledge about sexual transmission was low.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are aligned with those described by Vilela Borges et al., who evaluated knowledge and attitudes about pregnancy and contraception in the context of Zika virus in Brazil. In that study, health officials informed the public about Zika virus transmission and its health consequences, and providers knew about the congenital syndrome, but knowledge about sexual transmission was low.…”
Section: Discussionsupporting
confidence: 92%
“…Zika virus has profound consequences for women's SRH because it is sexually transmitted and carries high risks for pregnant women through mother‐to‐child transmission, which can cause microcephaly and other central nervous system anomalies . In addition, the emergence of Zika virus is related to environmental causes and climate change, which in turn influence the epidemic and women's SRH.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zika virus can also be transmitted during pregnancy from a woman to her fetus, and through unprotected sexual activity . A study in Brazil found high general awareness of the Zika virus, while women's knowledge about sexual transmission was low . The fact that this mosquito‐borne virus can also be transmitted through sexual contact makes it a unique public health challenge, adding to the risk of Zika infection among women.…”
Section: Introductionmentioning
confidence: 99%
“…A significant impact on the knowledge of the problem is living in regions directly related to a given infection. Among 526 women of childbearing age (18-49 years) living in the northeastern part of Brazil, as many as 98.6% knew that Zika virus causes congenital infections, but only half of them (50.2%) knew that the infection could be sexually transmitted [21]. In the majority of surveys conducted, awareness of CMV congenital infection was very low, and CMV infection was placed at the end of the listed, known diseases [16,17,18].…”
Section: Discussionmentioning
confidence: 99%